Coenzyme B induced coordination of coenzyme M via its thiol group to Ni(I) of F430 in active methyl-coenzyme M reductase. - Finazzo, C; Harmer, J; Bauer, C; Jaun, B; Duin, E; Mahlert, F; Goenrich, M; Thauer, R; Van Doorslaer, S; Schweiger, A (2003)
Methyl-coenzyme M reductase (MCR) catalyzes the reaction of methyl-coenzyme M (CH3-S-CoM) with coenzyme B (HS-CoB) to methane and CoM-S-S-CoB. At the active site, it contains the nickel porphinoid F430, which has to be in the Ni(I) oxidation state for the enzyme to be active. How the substrates interact with the active site Ni(I) has remained elusive. We report here that coenzyme M (HS-CoM), which is a reversible competitive inhibitor to methyl-coenzyme M, interacts with its thiol group with the Ni(I) and that for interaction the simultaneous presence of coenzyme B is required. The evidence is based on X-band continuous wave EPR and Q-band hyperfine sublevel correlation spectroscopy of MCR in the red2 state induced with 33S-labeled coenzyme M and unlabeled coenzyme B.